Malignant renal angiomyolipoma without tuberous sclerosis. (30th April 2014) - Cusano, Antonio; Abarzua-Cabezas, Fernando; Meraney, Anoop
Abstract : A 68-year-old woman presented with abdominal pain, fatigue, anorexia and night sweats. Imaging studies identified a vascular mass extending from the upper pole of the right kidney with anterior displacement to the abdominal midline, consistent with renal cell carcinoma. A radical nephrectomy and right pelvic lymph node dissection was performed. Pathology determined a grade 4 malignant epithelioid angiomyolipoma that invaded hilar and perinephric adipose tissue. Gross tumour was also present within the renal vein, sinus, pelvis, capsule and perinephric fat. The tumour was HMB-45 positive, supporting the diagnosis of a typical angiomyolipoma in association with the high-grade epithelioid tumour.